Influence of root application of microelements (B, Zn) on the state of the pigmental complex of tea leaves (Camellia sinensis (L.) O. Kuntze) - Z. V. Pritula; L. S. Malyukova; A. V. Velikiy (Новые технологии)
The influence of the root application of boron and zinc on the state of the pigment system of assimilating young and mature leaves of Samellia sinensis (L.) O. Kuntze evergreen shrub of different has been studied in natural conditions of the humid-subtropical zone of Russia. An increase in the stock of chlorophylls and carotenoids from July to October-November has been revealed. The ratio of chlorophyll a / v varied during the growing season in the range of 1.22-2.56 and was higher in variants with the use of microelements. The quantitative content of photosynthetic pigments in summer when using boron and zinc in mature leaves was commensurate or reliably below the control, in contrast to the autumn one, where the chlorophyll a content was higher. The dynamics of the restoration of the pigment fund in the summer-autumn period was more intensive in variants with the use of boron and zinc. Functional activity, estimated by the index of slow induction of chlorophyll fluorescence, “viability index”, was assessed as higher in comparison with the control one.